Sensory profile variation of pomegranate seeds and pomegranate juice : tea beverages flavor and acceptance - Higa, Federica A. (Kansas State University, 2016)
Pomegranate fruits have grown in popularity due to their known beneficial health properties. The objectives of this study were to: 1) determine if flavor differences existed among and within fruits, 2) understand appropriate numbers of replications needed for products that are naturally variable, and 3) compare individual and consensus scores for descriptive sensory analysis over 10 replications of the same product to determine whether differences are found between the methods. Three different sections of the pomegranate fruit were individually evaluated (top, middle and bottom) to determine if flavor differences existed among the fruit sections. Furthermore, the number of repetitions needed in order to obtain small differences in a descriptive panel was calculated. Results showed that pomegranate fruits have natural variation of flavor in the different sections, as well as differences among fruits of the same cultivar. The number of repetitions increased as the differences that wanted to be detected became smaller, and they decreased, as these differences increased. After each sections of fruit were individually evaluated, the panel discussed results and set consensus scores for each attribute. Analysis on mean individual scores and consensus data, along with Principal Component Analysis (PCA) showed that both, individual and consensus methods, provided the same reliable and reproducible information. However, this was evaluated using highly trained panelists. Besides pomegranate juice (PJ), green tea (GT) is one of the most consumed beverages in the world, and has the highest polyphenol content of all teas. Six PJ and GT blends were prepared at different ratios: 90-10, 80-20, 70-30, 60-40, 50-50, 40-60 vol/vol. Lipton GT and Wonderful pomegranates were used to prepare the samples. The objectives of this study were to: 1) determine sensory differences in the samples, 2) consumer acceptance before and after antioxidant information of the samples was provided, and 3) determine their total phenolic content (TPC). Results showed that samples with lower PJ were higher in attributes intensities for Green, and Tea like flavor, while attributes like Berry, Cranberry, Cherry and Sweetness were lower. Consumers liked samples higher in PJ, and sample 40-60 was the least liked. However, overall liking of all samples increased when antioxidant information was given. TPC results showed that pure PJ had the highest content, and as it was mixed with GT, TPC was the sum of the individual percentages of each component. Addition of claims in beverage labels might be a good strategy for consumers to purchase these type of products high in antioxidant content.
Keywords: Sensory analysis; Pomegranate seeds; Pomegranate juice - green tea; Flavor; Consumer acceptance; Total phenolic content